Alternative für Deutschland - The AfD : Germany's new Nazis or another populist party? - Klikauer, Thomas, 1962- (Sussex Academic Press, 2020)
Right-wing populism has been on the rise in Europe and elsewhere. Germany's foremost populist party is called Alternative for Germany (AfD). Founded in 2013 and entering Germany's federal parliament in 2017, the AfD increasingly moved towards right-wing extremism. Following the populist playbook, the AfD started off with a simple neoliberal and anti-Europe message, but soon moved towards the extreme right. By 2017 the AfDs ultra-nationalistic wing had successfully outmanoeuvred the party's moderate and neoliberal leader Frauke Petry. The author illuminates the party's ideological and institutional links to present-day Neo-Nazis; its close associations to the right-wing street movement Pegida; the recruitment of right-wing extremists and former Neo-Nazis into its parliamentarian ranks; its xenophobic, anti-Muslim, racist and anti-Semitic ideologies; and its relationship to the neo-fascist Identity Movement. The work engages with the make-up of AfD voters and electoral successes; the party's relationship to anti-Semitism; and its dreams of re-establishing a mythical Aryan Volksgemeinschaft. Close attention is paid to the AfDs demagogic and nationalistic leader, Björn Höcke, as well as the party's admiration for the radical right of neighbouring Austria. Three questions are posed: Will the AfD lead to the end of German democracy? Is Germany moving towards another Third Reich? Is there another Hitler in the making?